Research Learning for Young Researchers Madrasahs in Indonesia - Munawaroh, Diah Ambarumi; Suwardi (FKDP (Forum Komunikasi Dosen Peneliti), 2022)
Research learning in madrasahs is a forum to encourage students' talents and interests in the field of scientific research. The concept of research madrasah is the development of madrasahs through learning innovations, namely the implementation of research, where students become young researchers in research exercises, with topics related to science in accordance with the subjects obtained. Prof. Mary Kellet explained that children who are involved in the research process are able to explore creativity and innovation by accessing rich resources with critical thinking skills, and analytical abilities. Prof. Pricilia Anderson explained working with children in research by understanding their views and experiences and providing rights opportunities for children and adults in the form of improving their knowledge and skills. Prof. Pia Christensen stated the importance of establishing a culture of communication between young researchers and adult researchers in understanding the world from their point of view.